2015
DOI: 10.1093/infdis/jiv200
|View full text |Cite
|
Sign up to set email alerts
|

Does Influenza Vaccination Modify Influenza Severity? Data on Older Adults Hospitalized With Influenza During the 2012−2013 Season in the United States

Abstract: Our findings show a modest effect of influenza vaccination on disease severity. Analysis of data from seasons with different predominant strains and higher estimates of vaccine effectiveness are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 48 publications
4
39
1
Order By: Relevance
“…Our findings are consistent with the view that inactivated influenza vaccines provide moderate protection against infection but do not provide any additional protection against severe disease requiring hospitalization if breakthrough infection (vaccine failure) occurs [27,28]. …”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with the view that inactivated influenza vaccines provide moderate protection against infection but do not provide any additional protection against severe disease requiring hospitalization if breakthrough infection (vaccine failure) occurs [27,28]. …”
Section: Discussionsupporting
confidence: 90%
“…We had previously assessed the effect of influenza vaccination on disease severity among adults aged 50 years and older during the 2012–13 season using a similar analytical approach [5]. In that study, we did not find a substantial effect of vaccination on clinical outcomes (we only found a modest effect of vaccination on ICU LOS in the 50–64 year olds).…”
Section: Discussionmentioning
confidence: 82%
“…However, some studies have suggested that influenza vaccination could modify the severity of illness among vaccinated patients who subsequently develop influenza virus infection [58]. Evidence for vaccine modification of influenza-associated disease severity could be an important argument toward improving influenza vaccination coverage in various groups of the population.…”
mentioning
confidence: 99%
“…However, several studies have reported influenza vaccine effectiveness in reducing illness severity, including reducing severe illness in persons aged > 65 years [39], and reducing in-hospital mortality and ICU admissions for those aged 18-49 years and > 65 years compared to unvaccinated individuals [40]. One study reported that duration of ICU hospitalization was reduced a half-day in patients aged 50-64 years who had received influenza vaccination compared with unvaccinated patients [41]. A study across all age groups in Spain reported influenza VE of 58% in reducing the risk of severe influenza requiring hospitalization [42].…”
Section: Prevention and Vaccinationmentioning
confidence: 99%